Functional traits and environmental conditions predict community isotopic niches and energy pathways across spatial scales - Dézerald, Olivier; Srivastava, Diane S.; Céréghino, Régis; Carrias, Jean-François; Corbara, Bruno; Farjalla, Vinicius F.; Leroy, Céline; Marino, Nicholas A. C.; Piccoli, Gustavo C. O. [UNESP]; Richardson, Barbara A.; Richardson, Michael J.; Romero, Gustavo Q.; et al. (Wiley, 2018)
Despite ongoing research in food web ecology and functional biogeography, the links between food web structure, functional traits and environmental conditions across spatial scales remain poorly understood. Trophic niches, defined as the amount of energy and elemental space occupied by species and food webs, may help bridge this divide. Here, we ask how the functional traits of species, the environmental conditions of habitats and the spatial scale of analysis jointly determine the characteristics of trophic niches. We used isotopic niches as a proxy of trophic niches, and conducted analyses at spatial scales ranging from local food webs and metacommunities to geographically distant sites. We sampled aquatic macroinvertebrates from 104 tank bromeliads distributed across five sites from Central to South America and compiled the macroinvertebrates’ functional traits and stable isotope values (δ15N and δ13C). We assessed how isotopic niches within each bromeliad were influenced by the functional trait composition of their associated invertebrates and environmental conditions (i.e., habitat size, canopy cover [CC] and detrital concentration [DC]). We then evaluated whether the diet of dominant predators and, consequently, energy pathways within food webs reflected functional and environmental changes among bromeliads across sites. At last, we determined the extent to which the isotopic niches of macroinvertebrates within each bromeliad contributed to the metacommunity isotopic niches within each site and compared these metacommunity-level niches over biogeographic scales. At the bromeliad level, isotopic niches increased with the functional richness of species in the food web and the DC in the bromeliad. The diet of top predators tracked shifts in prey biomass along gradients of CC and DC. Bromeliads that grew under heterogeneous CC displayed less trophic redundancy and therefore combined to form larger metacommunity isotopic niches. At last, the size of metacommunity niches depended on within-site heterogeneity in CC. Our results suggest that the trophic niches occupied by food webs can predictably scale from local food webs to metacommunities to biogeographic regions. This scaling process is determined by both the functional traits of species and heterogeneity in environmental conditions. A plain language summary is available for this article.
Keywords: energy pathways; environmental heterogeneity; food webs; functional biogeography; functional diversity; isotopic niche; metacommunity; trophic structure